Medium‐Sized‐Ring Analogues of Dibenzodiazepines by a Conformationally Induced Smiles Ring Expansion. (16th October 2017) - Costil, Romain; Lefebvre, Quentin; Clayden, Jonathan
Abstract: Analogues of dibenzodiazepines, in which the seven‐membered nitrogen heterocycle is replaced by a 9–12‐membered ring, were made by an unactivated Smiles rearrangement of five‐ to eight‐membered heterocyclic anthranilamides. The conformational preference of the tertiary amide in the starting material leads to intramolecular migration of a range of aryl rings, even those lacking electron‐withdrawing activating groups, and provides a method for n → n +4 ring expansion. The medium‐ring products adopt a chiral ground state with an intramolecular, transannular hydrogen bond. The rate of interconversion of their enantiomeric conformers depends on solvent polarity. Ring size and adjacent steric hindrance modulate this hidden hydrophilicity, thus making this scaffold a good candidate for drug development.